A comparative study on the use of calibrated and rainbow schlieren techniques in axisymmetric supersonic jets - Mariani, Raffaello (2020)
Detailed experimental comparisons had been conducted between calibrated and rainbow schlieren on perfectly- and under-expanded axisymmetric supersonic jets through a modified Z-type schlieren system. The techniques were implemented by using a weak lens in the field-of-view to provide calibration information for the extraction of quantitative density gradients from the experimental schlieren images. Sixth-order polynomial curve fits were obtained for both calibrated and rainbow schlieren respectively. The effects of light inhomogeneity caused by the mirrors and system diaphragm aperture had been evaluated for the colour images and results indicate that averaging the background hue is an acceptable approach for minimizing light variations with less than 2% experimental error. Density gradients as calculated via Abel transform have also been evaluated to validate the two different set-ups. Additionally, experimental results have been compared to validated numerical results and they show that calibrated schlieren is able to predict density gradients within 2% of the numerical results. This is significantly more superior to rainbow schlieren, where errors in the estimated density gradients are closer to 20%. It is shown here that rainbow schlieren results are more adversely impacted by the system diaphragm aperture, especially for vertical light cut-off configuration. This is partly due to the loss of sensitivity of the schlieren system, as well as potential light diffusion caused by the filter.